PENGARUH KINERJA LINGKUNGAN, KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, PROFITABILITAS DAN LEVERAGE TERHADAP CARBON EMISSION DISCLOSURE (STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020) - Dita Arum Almuaromah; Wahyono Wahyono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Carbon Emission Disclosure is an entity's contribution to environmental and climate change, especially global warming. The existence of a business entity certainly cannot be separated from the community environment, so that the place of company activities is required to be in line with the values ​​and norms that apply in the community. This causes an increase in the need for information related to environmental disclosure, especially the disclosure of carbon emissions. This study aims to determine the effect of environmental performance, institutional ownership, managerial ownership, profitability and leverage on carbon emission disclosures in mining companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling technique in this study used purposive sampling. The research sample consisted of 7 mining companies. The data analysis method used is multiple linear regression analysis. The results of this study indicate that institutional ownership and profitability have an effect on carbon emission disclosures. Meanwhile, environmental performance, managerial ownership and leverage have no effect on carbon emission disclosures.